Overview and analysis of safety management in prefabricated construction (2012–2022) - Li, Clyde Zhengdao; Yu, Qingyi; Tam, Vivian W. Y.; Wu, Hengqin (Journal of Civil Engineering and Management, 2026)
The stable development of the construction industry plays a significant role in national economic growth. With the continuous reform and progress of the construction industry, construction safety has become a vital issue of concern and emphasis. As an essential means for the sustainable development of the construction industry and industrialization of construction, prefabrication has the advantages of reducing waste of resources and improving construction safety and efficiency and is strongly promoted by the construction industry around the world. Although the safety management of traditional construction has been fully researched, the traditional safety management mode cannot be directly applied to assembled construction because of differences in their construction characteristics and management scopes. Thus, investigating the safety issues of prefabrication is necessary. Although numerous scholars analyzed safety in the different construction stages of assembled buildings, many connections and contents in the literature must be summarized, and systematic literature research must be conducted. Therefore, this study uses a systematic and comprehensive review approach to fill the research gaps. In the first stage, 107 papers related to prefabrication safety management published, meeting the requirements are selected through a literature search. In the second stage, scientometric analysis is conducted to identify the journal sources, scholars, regions, and keywords. In the final stage, content analysis is performed to achieve three main objectives: 1) to identify the differences between prefabricated and conventional buildings and summarize the characteristics of prefabricated buildings (PBs) to obtain the characteristics of prefabrication safety management, 2) to summarize the research topics, and 3) to discuss and provide signposts for potential research directions. This study provides a comprehensive knowledge framework that links current research areas with future research trends, thereby providing a multidisciplinary guide to researchers to gain insights from the latest research on prefabrication safety management.